PENGARUH POLA MAKAN DAN INDEKS MASSA TUBUH TERHADAP PENINGKATAN TEKANAN DARAH PADA USIA DEWASA: Studi Literatur - Ulfa Aeni (2020)
Background: Hypertension is a disease that can be seen from elevated blood pressure. The prevention of hypertension is necessary because hypertension is the most infectious disease burden in the world. If hypertension is not treated immediately, it can cause other diseases such as cardiovascular, CVD, stroke, ischemic heart and chronic kidney failure. Purpose: analyzing the effects of diet and body mass indexes on increased blood pressure in adult age. Method: with the study of literature review that has been analyzed based on a topic related to resource sources taken out in 2015 to 2020. Using words "hypertension or boold pressure", "adults or adults", "dietary approaches or eating", "body mass index". Results: based on 30 journals revised diet such as sodium and fat can increase blood pressure whereas, foods containing green vegetables, fruits, nuts can lower blood pressure. Excess body mass indexes ( > 25 kg/m2) are more likely to have increased blood pressure. Analysis: using jonhson's theory as a supporting theory in the study. This theory explains the importance of maintaining health behaviors to prevent an increase in blood pressure. Conclusion: increased blood pressure can result from increased consumption of foods that contain fats, excess sodium And excess body mass indexes can also cause increased blood pressure.